Uv curable quantum dot sealant and preparation method thereof

CN122898244APending Publication Date: 2026-10-13GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611390169.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,上述现有专利技术中的密封胶仍存在以下不足:(1)该密封胶为双组分体系,各组分需预先分别合成树脂并配制,使用时再按严格比例混合,工序繁琐,不利于工业化高效生产;(2)有机硅环氧量使用量较大,大量环氧树脂固化时体积收缩与应力集中效应明显,导致密封胶膜质地较脆,在长期使用或冷热冲击老化过程中易产生应力开裂,同时存在与高阻隔膜之间粘接失效的风险,虽然增加B组分可提升柔韧性,但随着B组分添加量的增加,密封胶的透光率和耐紫外老化性能显著下降,即柔韧性/粘附性与光学/耐候性之间存在难以调和的矛盾;(3)采用阳离子-自由基混杂固化,但阳离子光引发剂及光敏化剂价格昂贵,增加了原料成本;且阳离子固化活性较低、固化速度慢,降低了流水线生产效率;(4)该专利中两种树脂的分子结构均以线型两端带有光活性基团为主,光固化交联位点密度有限,若能将光活性基团引入聚合物侧链或构建长支链末端结构,则不仅能提升树脂对纳米量子点的浸润性与分散稳定性,减少团聚猝灭,还可大幅增加单位质量树脂的光反应位点密度,从而在固化后形成更致密的交联网络,进一步提升密封胶的阻隔性能与耐老化能力

Benefits of technology

本发明采用单组分自由基光固化体系,通过将有机硅改性聚氨酯树脂、活性稀释剂和光引发剂直接复配,省去了双组分体系使用前严格混合的繁琐工序,大幅简化了制备流程,显著提升了工业化生产效率,同时避免了阳离子光引发剂及光敏化剂的高昂成本,且自由基固化活性高、速度快,有效提高了流水线产能;在树脂分子结构设计上,本发明摒弃了易导致脆裂和粘接失效的环氧树脂体系,转而以聚醚多元醇、端双羟基硅油和二元醇共同改性聚氨酯,形成聚氨酯主链与有机硅侧链的嵌段结构,既赋予密封胶优异的柔韧性和内聚强度以缓解固化收缩应力,又通过有机硅链段增强了对量子点的浸润分散性及耐紫外老化性能,解决了密封胶柔韧性/粘附性与光学/耐候性之间的矛盾;而且二元醇的引入及后续封端反应在聚氨酯分子链上接枝了独特的长不饱和支链结构,大幅增加了光活性基团数量和交联网络密度,不仅提升了密封胶的水氧阻隔效果和耐老化性能,还使量子点获得更好的分散稳定性,有效避免量子点团聚猝灭,从而在保持密封胶高透光率的同时,实现了密封胶的制备工艺操作简单、成本经济、固化快速、力学柔韧、光学优异及长期可靠的优良综合性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898244A_ABST
    Figure CN122898244A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of quantum dot encapsulating material, and discloses a UV-curable quantum dot sealant and a preparation method thereof.The sealant comprises, by weight, 60-80 parts of organic silicon modified polyurethane resin, 20-40 parts of active diluent and 0.3-0.6 parts of photoinitiator; the pre-polymer is prepared by mixing isocyanate, polyether polyol, end dihydroxyl silicone oil and additives and heating; then, dihydric alcohol is added dropwise to react until the content of isocyanate groups is 1-2%, and a blocking agent is added until the isocyanate groups are completely consumed to obtain the organic silicon modified polyurethane resin.The application adopts a single-component system and uses a free radical photocuring mode, which not only has high production efficiency, but also has low raw material cost; the prepared unsaturated branched polyurethane resin can significantly improve the wettability and dispersibility of quantum dots, effectively avoid aggregation quenching, and the branched structure improves the crosslinking density of the system, thereby endowing the sealant with excellent water and oxygen barrier properties and aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of quantum dot encapsulation materials technology, specifically relating to a UV-curable quantum dot sealant and its preparation method. Background Technology

[0002] Quantum dot materials exhibit promising applications in high-end displays and mobile devices due to their advantages such as high color purity, wide color gamut, high brightness, high luminous efficiency, and long lifespan. Especially in the high-end display field, current mainstream quantum dot enhancement films and quantum dot color filters are essentially quantum dot optical films, with a core structure of a sandwich composite film consisting of a quantum dot layer, sealant, and high-barrier film. In this structure, the sealant plays a crucial role. It must not only effectively disperse the quantum dots, preventing aggregation, quenching, or sedimentation, but also maintain its sealing performance under normal operating conditions after curing, preventing moisture and oxygen from corroding the quantum dots and reducing the device's luminous efficiency. Therefore, the performance of the sealant material directly affects the lifespan of the quantum dot display.

[0003] Ultraviolet (UV) curing technology has become the ideal curing method for quantum dot sealants due to its advantages such as being green, efficient, and avoiding the thermal failure of quantum dots. Currently, domestically produced high-end quantum dot display products suffer from high costs and insufficient competitiveness. Therefore, it is of great significance to develop UV-curable sealants that can effectively disperse luminescent quantum dots, primarily CdSe and InP quantum dots, possess excellent water and oxygen barrier properties, outstanding aging resistance, and provide long-term protection for quantum dots, thus extending their lifespan.

[0004] Chinese Patent Publication No. CN110527436A discloses a special sealant for quantum dot encapsulation. The sealant is obtained by uniformly mixing components A and B in a mass ratio of 4:1 to 2:1. Component A contains 60 to 80 parts of silicone epoxy resin, 20 to 40 parts of reactive diluent, 2 to 5 parts of cationic photocuring component (photoacid generator), and 0.2 to 0.6 parts of photosensitizer. Component B contains 60 to 80 parts of polyurethane-modified silicone resin, 20 to 40 parts of acrylate reactive diluent, and 2 to 6 parts of free radical photoinitiator. The sealant exhibits good compatibility with quantum dots, minimal impact on the fluorescence brightness of quantum dots, excellent aging resistance, good adhesion, and excellent environmental reliability. However, the sealant in the above-mentioned existing patented technology still has the following shortcomings: (1) The sealant is a two-component system, and each component needs to be synthesized and formulated separately in advance. When used, they are mixed in strict proportions, which is cumbersome and not conducive to efficient industrial production; (2) The amount of silicone epoxy used is large. When a large amount of epoxy resin is cured, the volume shrinkage and stress concentration effect are obvious, resulting in a brittle sealant film. It is prone to stress cracking during long-term use or thermal shock aging. At the same time, there is a risk of adhesion failure between it and the high barrier film. Although adding component B can improve flexibility, as the amount of component B added increases, the light transmittance and UV aging resistance of the sealant decrease significantly. That is, there is a gap between flexibility / adhesion and optical / weather resistance. (3) The use of cationic-free radical hybrid curing is expensive, which increases the cost of raw materials; and the low activity and slow curing speed of cationic curing reduces the efficiency of production line; (4) The molecular structure of the two resins in this patent is mainly linear with photoactive groups at both ends, and the density of photocuring crosslinking sites is limited. If the photoactive groups can be introduced into the polymer side chain or a long branch end structure can be constructed, it can not only improve the wettability and dispersion stability of the resin to the nano quantum dots and reduce agglomeration quenching, but also greatly increase the photoreaction site density per unit mass of resin, thereby forming a denser crosslinking network after curing, further improving the barrier performance and aging resistance of the sealant. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a UV-curable quantum dot sealant and its preparation method. The quantum dot sealant of this invention contains only one polyurethane resin with an unsaturated long side-branched structure. This resin has good compatibility and dispersibility with quantum dots, achieving lower UV aging degradation without sacrificing barrier properties. Furthermore, this quantum dot sealant does not contain a second component, silicone-modified epoxy resin, and does not require cationic photocuring. Therefore, the process is simple, the cost is low, and the curing efficiency is higher.

[0006] One objective of this invention is to provide a UV-curable quantum dot sealant, comprising, by weight, the following components: 60-80 parts of silicone-modified polyurethane resin, 20-40 parts of reactive diluent, and 0.3-0.6 parts of photoinitiator; The preparation method of the organosilicon-modified polyurethane resin includes the following steps: Weigh the following raw materials according to the following weight proportions: 20-50 parts isocyanate, 40-80 parts polyether polyol, 10-30 parts diol, 10-30 parts terminal dihydroxyl silicone oil, 0.1-1 part catalyst, 0.1-1 part polymerization inhibitor, 0.1-0.5 parts antioxidant, and 3-6 parts end-capping agent; The polyether polyol was subjected to vacuum dehydration and cooled for later use. Isocyanate, vacuum-dehydrated polyether polyol, terminal dihydroxyl silicone oil, polymerization inhibitor, antioxidant and catalyst are mixed evenly and then heated to react to obtain prepolymer; Diol is slowly added dropwise to the prepolymer, and the reaction continues. When the mass percentage of isocyanate groups in the system is 1%~2%, a capping agent is added to the system, and the reaction continues until the isocyanate groups are completely consumed. Unreacted capping agent is removed under reduced pressure to obtain the silicone-modified polyurethane resin. The infrared spectrum of the obtained silicone-modified polyurethane resin is shown below. Figure 2 As shown, by Figure 2 It can be seen that at 805cm -1 With 1641cm -1 The peak at 1027 cm⁻¹ is a characteristic peak of unsaturated carbon double bonds, indicating that the photocurable long unsaturated branched structure has been successfully introduced into polyurethane; -1 The absorption peak near the Si-O stretching vibration is 1734 cm⁻¹. -1 The peak at this location is the C=O stretching vibration peak. 3363cm -1 and 1536cm -1 The absorption peaks at 2270 cm⁻¹ are for the NH stretching vibration and in-plane bending vibration, respectively. -1 The absence of NCO characteristic peaks in the vicinity indicates that the isocyanate reaction was complete, thus confirming that the synthesized product has the expected structure.

[0007] Furthermore, the conditions for vacuum dehydration of polyether polyols are as follows: first, vacuum dehydration is carried out at 120°C for 3-4 hours, and then cooled to 60°C-70°C.

[0008] Furthermore, isocyanate, vacuum-dehydrated polyether polyol, terminal hydroxyl silicone oil, polymerization inhibitor, antioxidant and catalyst are first stirred evenly at 60~75℃, and then heated to 85℃ and kept at that temperature for 2 hours to obtain prepolymer.

[0009] Furthermore, the diol was slowly added dropwise to the prepolymer over 0.5 hours, and the reaction continued for 2 to 3 hours.

[0010] Furthermore, the reactive diluent is selected from one or more of the following: isobornyl acrylate, dicyclopentadiene acrylate, tricyclodecanediethanol diacrylate, tetrahydrofuran acrylate, cyclotrimethylolpropane formal acrylate, dicyclopentadiene methacrylate, ethylene glycol dicyclopentenyl ether acrylate, dicyclopentadiene oxyethyl acrylate, and tricyclodecanediethanol diacrylate.

[0011] Furthermore, the photoinitiator is a cleavage-type free radical catalyst selected from one or more of the following: 2-hydroxy-2-methylphenylpropanone (Darocur 1173), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (Irgacure 819), and 1-hydroxy-cyclohexyl-phenyl ketone (Irgacure 184).

[0012] Further, the isocyanate is selected from one or more of isoflurane diisocyanate, hexamethylene diisocyanate, 4,4-diisocyanate dicyclohexylmethane, tetramethyl isophthalimethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, isophthalic dimethyl diisocyanate, and naphthalene 1,5-diisocyanate.

[0013] Furthermore, the average molecular weight of the polyether polyol is 400-2000, and it is selected from one or more of polypropylene glycol, polyethylene glycol, polytetrahydrofuran glycol, and polypropylene oxide.

[0014] Furthermore, the terminal hydroxyl silicone oil is selected from one or two of hydroxyl-terminated polydimethylsiloxane and α,ω-dihydroxypolydimethylsiloxane.

[0015] Furthermore, the catalyst is selected from at least one of organometallic catalysts including stannous isooctanoate, stannous octanoate, dibutyltin dilaurate, bismuth isooctanoate, bismuth laurate, bismuth neodecanoate, and tetraisopropyl titanate. Furthermore, the method for preparing the diol includes the following steps: Weigh the following raw materials in the indicated weight proportions: 25-50 parts of bio-based dicarboxylic acid, 50-100 parts of glycidyl oleate, 0.1-1 part of catalyst, 0.1-0.5 parts of polymerization inhibitor, and 0.1-0.5 parts of antioxidant, wherein the molar ratio of bio-based dicarboxylic acid to glycidyl oleate is 1:2; The bio-based dicarboxylic acid, after vacuum dehydration, is mixed with glycidyl oleate, a polymerization inhibitor, an antioxidant, and catalyst 1. Under inert gas protection, the mixture is reacted at 105°C for 1-2 hours until the system is homogeneous. The temperature is then raised to 110°C and held for 3-4 hours. Finally, the temperature is lowered to 85-95°C and the reaction is carried out under reduced pressure for 1 hour to obtain the diol. The chemical structural formula of the obtained diol is as follows: Figure 1 As shown, R is a bio-based dicarboxylic acid monomer.

[0016] Further, the bio-based dicarboxylic acid is selected from one or more of succinic acid, glutaric acid, lauryl acid, sebacic acid, and itaconic acid; the glycidyl oleate is selected from 2,3-epoxypropyl octadecenoic acid; and the catalyst 1 is selected from at least one of triphenylphosphine, tetrabutylammonium bromide, triethylbenzylammonium bromide, and phenyltrimethylammonium bromide.

[0017] Further, the polymerization inhibitor is selected from one or more of p-methoxyphenol, hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, and bisphenol A; the antioxidant is selected from one or more of antioxidant 2246, antioxidant 1076, antioxidant 1010, and antioxidant 168; and the end-capping agent is selected from one or more of ethanol, n-propanol, 2-(tert-butylamino)ethyl methacrylate, hydroxyethyl acrylate, and hydroxyethyl methacrylate.

[0018] The second objective of this invention is to provide a method for preparing the above-mentioned UV-curable quantum dot sealant, comprising the following steps: mixing the self-made silicone-modified polyurethane resin, reactive diluent and photoinitiator evenly according to the above-mentioned weight proportions to obtain the UV-curable quantum dot sealant.

[0019] Compared with the prior art, the present invention has the following beneficial effects: This invention employs a single-component free radical photocuring system. By directly compounding organosilicon-modified polyurethane resin, reactive diluent, and photoinitiator, it eliminates the cumbersome process of strict mixing before use in two-component systems, significantly simplifying the preparation process and greatly improving industrial production efficiency. It also avoids the high costs of cationic photoinitiators and photosensitizers. Furthermore, the free radical curing activity is high and the speed is fast, effectively increasing production line capacity. In terms of resin molecular structure design, this invention abandons epoxy resin systems that easily lead to brittleness and adhesive failure. Instead, it uses polyether polyol, terminal dihydroxyl silicone oil, and diol to jointly modify polyurethane, forming a block structure of polyurethane main chain and organosilicon side chains. This endows the sealant with excellent flexibility and cohesive strength. By alleviating curing shrinkage stress and enhancing the wetting and dispersibility of quantum dots and UV aging resistance through organosilicon segments, the contradiction between the sealant's flexibility / adhesion and optical / weather resistance is resolved. Moreover, the introduction of diol and subsequent end-capping reaction graft a unique long unsaturated branched structure onto the polyurethane molecular chain, significantly increasing the number of photoactive groups and the density of the crosslinking network. This not only improves the sealant's water and oxygen barrier effect and aging resistance but also gives the quantum dots better dispersion stability, effectively preventing quantum dot aggregation and quenching. Thus, while maintaining the sealant's high light transmittance, it achieves excellent comprehensive performance with simple preparation process, cost-effectiveness, rapid curing, mechanical flexibility, excellent optical properties, and long-term reliability. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the chemical structure of the diol prepared in this invention; Figure 2 The infrared spectrum of the organosilicon-modified polyurethane resin prepared in this invention. Detailed Implementation

[0021] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings.

[0022] Unless otherwise specified, all reagents used in this invention are commercially available, and all methods used are conventional techniques in the art.

[0023] Example 1 A UV-curable quantum dot sealant comprising the following components in parts by weight: 60 parts of silicone-modified polyurethane resin, 40 parts of dicyclopentadiene acrylate, 3 parts of Darocur 1173, and 1 part of TPO.

[0024] The preparation method of silicone-modified polyurethane resin includes the following steps: By weight, 90 parts of polytetrahydrofuran diol with a molecular weight of 2000 were added to a three-necked flask equipped with a magnetic stirrer, thermometer, and vacuum device. Stirring was started, and the mixture was vacuum-dehydrated at 120°C for 4 hours. After cooling to 60°C, the mixture was transferred to a four-necked flask equipped with a stirrer, thermometer, reflux condenser, and constant pressure funnel. Subsequently, 10 parts of α,ω-dihydroxypolydimethylsiloxane (3% by mass of hydroxyl groups), 30 parts of isophorone diisocyanate, 0.4 parts of p-methoxyphenol, and antioxidant 1010 were added sequentially. 0.4 parts of stannous isooctanoate and 0.5 parts of stannous isooctanoate were mixed evenly by high-speed stirring at 60°C, and the mixture was heated to 85°C and reacted for 2 hours to obtain a prepolymer. 20 parts of diol were weighed and slowly added dropwise to the prepolymer, with the addition time controlled at 0.5 hours. The reaction was continued for 3 hours. The content of the remaining isocyanate groups in the system was measured by the n-butyldiamine method. When the content of isocyanate groups was less than 2%, ethanol was added to the system for end-capping. The reaction was continued until the isocyanate groups in the system were completely consumed. The system was depressurized for 0.5 hours to remove unreacted ethanol. The product was then discharged to obtain the silicone-modified polyurethane resin.

[0025] The preparation method of diols includes the following steps: First, succinic acid was placed in a vacuum oven at 80°C to remove all moisture and set aside. Then, by weight, 15 parts of the vacuum-dehydrated succinic acid, 85 parts of glycidyl oleate, 0.3 parts of p-methoxyphenol, 0.3 parts of antioxidant 1010, and 0.5 parts of triphenylphosphine were weighed and added to a well-sealed reaction vessel equipped with a magnetic stirrer, thermometer, and nitrogen inlet. Stirring was started, and after 15 minutes of reduced pressure, nitrogen was introduced to remove air. The reaction was carried out at 105°C for 1.5 hours, then the temperature was raised to 110°C and the reaction continued for 3 hours. The temperature was then lowered to 90°C and the reaction was carried out under reduced pressure for 1 hour before being discharged to obtain the diol. The prepared diol was then transferred to a dry, opaque container for storage and later use.

[0026] A method for preparing a UV-curable quantum dot sealant is as follows: silicone-modified polyurethane resin, dicyclopentadiene acrylate, Darocur 1173 and TPO are mixed evenly according to the above weight parts to obtain the UV-curable quantum dot sealant.

[0027] Example 2 A UV-curable quantum dot sealant comprising the following components in parts by weight: 70 parts silicone-modified polyurethane resin, 30 parts dicyclopentadiene acrylate, 3 parts Darocur 1173, and 1 part TPO.

[0028] A method for preparing a UV-curable quantum dot sealant is as follows: silicone-modified polyurethane resin, dicyclopentadiene acrylate, Darocur 1173 and TPO are mixed evenly according to the above weight parts to obtain the UV-curable quantum dot sealant.

[0029] The preparation methods of the organosilicon-modified polyurethane resin and diol in this embodiment are the same as those in Example 1.

[0030] Example 3 A UV-curable quantum dot sealant comprising the following components in parts by weight: 80 parts of self-made silicone-modified polyurethane resin, 20 parts of dicyclopentadiene acrylate, 3 parts of Darocur 1173, and 1 part of TPO.

[0031] A method for preparing a UV-curable quantum dot sealant is as follows: silicone-modified polyurethane resin, dicyclopentadiene acrylate, Darocur 1173 and TPO are mixed evenly according to the above weight parts to obtain the UV-curable quantum dot sealant.

[0032] The preparation methods of the organosilicon-modified polyurethane resin and diol in this embodiment are the same as those in Example 1.

[0033] Example 4 A UV-curable quantum dot sealant comprising the following components in parts by weight: 70 parts of self-made silicone-modified polyurethane resin, 30 parts of dicyclopentadiene acrylate, 3 parts of Darocur 1173, and 1 part of TPO.

[0034] A method for preparing a UV-curable quantum dot sealant is as follows: silicone-modified polyurethane resin, dicyclopentadiene acrylate, Darocur 1173 and TPO are mixed evenly according to the above weight parts to obtain the UV-curable quantum dot sealant.

[0035] In this embodiment, the amount of diol added during the preparation of the silicone-modified polyurethane resin is 15 parts by weight, and the remaining steps are the same as those in Example 1.

[0036] The preparation method of the diol in this embodiment is the same as that in Example 1.

[0037] Example 5 A UV-curable quantum dot sealant comprising the following components in parts by weight: 70 parts silicone-modified polyurethane resin, 30 parts dicyclopentadiene acrylate, 3 parts Darocur 1173, and 1 part TPO.

[0038] A method for preparing a UV-curable quantum dot sealant is as follows: silicone-modified polyurethane resin, dicyclopentadiene acrylate, Darocur 1173 and TPO are mixed evenly according to the above weight parts to obtain the UV-curable quantum dot sealant.

[0039] In this embodiment, the amount of diol added during the preparation of the silicone-modified polyurethane resin is 25 parts by weight, and the remaining steps are the same as those in Example 1.

[0040] The preparation method of the diol in this embodiment is the same as that in Example 1.

[0041] Example 6 A UV-curable quantum dot sealant comprising the following components in parts by weight: 70 parts of silicone-modified polyurethane resin, 30 parts of tricyclodecanediethanol diacrylate, 3 parts of Darocur 1173, and 1 part of TPO.

[0042] A method for preparing a UV-curable quantum dot sealant is as follows: silicone-modified polyurethane resin, tricyclodecanediethanol diacrylate, Darocur 1173 and TPO are mixed evenly according to the above weight parts to obtain the UV-curable quantum dot sealant.

[0043] The preparation methods of the organosilicon-modified polyurethane resin and diol in this embodiment are the same as those in Example 1.

[0044] Example 7 A UV-curable quantum dot sealant comprising the following components in parts by weight: 70 parts of silicone-modified polyurethane resin, 15 parts of tricyclodecanediethanol diacrylate, 15 parts of dicyclopentadiene acrylate, 3 parts of Darocur 1173, and 1 part of TPO.

[0045] A method for preparing a UV-curable quantum dot sealant is as follows: silicone-modified polyurethane resin, tricyclodecanediethanol diacrylate, dicyclopentadiene acrylate, Darocur 1173 and TPO are mixed evenly according to the above weight parts to obtain the UV-curable quantum dot sealant.

[0046] The preparation methods of the organosilicon-modified polyurethane resin and diol in this embodiment are the same as those in Example 1.

[0047] Example 8 A UV-curable quantum dot sealant comprising the following components in parts by weight: 70 parts of self-made silicone-modified polyurethane resin, 30 parts of isoborneol acrylate, 3 parts of Darocur 1173, and 1 part of TPO.

[0048] A method for preparing a UV-curable quantum dot sealant is as follows: silicone-modified polyurethane resin, isoborneol acrylate, Darocur 1173 and TPO are mixed evenly according to the above weight parts to obtain the UV-curable quantum dot sealant.

[0049] The preparation methods of the organosilicon-modified polyurethane resin and diol in this embodiment are the same as those in Example 1.

[0050] Example 9 A UV-curable quantum dot sealant comprising the following components in parts by weight: 70 parts of self-made silicone-modified polyurethane resin, 30 parts of ethylene glycol dicyclopentenyl ether acrylate, 3 parts of Darocur 1173, and 1 part of TPO.

[0051] A method for preparing a UV-curable quantum dot sealant is as follows: silicone-modified polyurethane resin, ethylene glycol dicyclopentenyl ether acrylate, Darocur 1173 and TPO are mixed evenly according to the above weight parts to obtain the UV-curable quantum dot sealant.

[0052] The preparation methods of the organosilicon-modified polyurethane resin and diol in this embodiment are the same as those in Example 1.

[0053] Example 10 A UV-curable quantum dot sealant comprising the following components in parts by weight: 70 parts silicone-modified polyurethane resin, 30 parts dicyclopentadiene acrylate, 3 parts Darocur 1173, and 1 part Irgacure 184.

[0054] A method for preparing a UV-curable quantum dot sealant is as follows: silicone-modified polyurethane resin, dicyclopentadiene acrylate, Darocur 1173 and Irgacure 184 are mixed evenly according to the above weight parts to obtain the UV-curable quantum dot sealant.

[0055] The preparation methods of the organosilicon-modified polyurethane resin and diol in this embodiment are the same as those in Example 1.

[0056] Comparative Example 1 A UV-curable quantum dot sealant, whose composition and preparation method are the same as those in Example 1, except that the silicone-modified polyurethane resin is replaced with an equal amount of Sartoma Company's aliphatic polyurethane acrylate CN996.

[0057] Comparative Example 2 A UV-curable quantum dot sealant, whose composition and preparation method are the same as those in Example 1, except that the silicone-modified polyurethane resin is replaced with an equal amount of Sartoma Company's aliphatic polyurethane acrylate CN990.

[0058] Comparative Example 3 A UV-curable quantum dot sealant, with the same composition and preparation method as Example 1, differing only in that the silicone-modified polyurethane resin is replaced with an equal amount of Covestro AgiSyn.TM 670T1.

[0059] Comparative Example 4 A UV-curable quantum dot sealant, with the same composition and preparation method as Example 1, differs from Example 1 only in that the self-made silicone-modified polyurethane resin is replaced with an equal amount of Covestro NeoRad. TM U-6282.

[0060] The UV-curable quantum dot sealants prepared in Examples 1-10 and Comparative Examples 1-4 were subjected to performance tests, and the specific test results are shown in Table 1. The specific test methods for the above performance are as follows: 1. Hardness test of adhesive film: The UV-curable quantum dot sealants prepared in Examples 1-10 and Comparative Examples 1-4 were applied to the substrate using a four-sided coater, with a coating thickness of 30 μm. The adhesive film was then placed in a conveyor-type LED curing machine for curing. The light source wavelength was 365 nm and the light intensity was 500 mW / cm². 2 The irradiation time was 5 seconds. The cured film was tested according to GB / T 6739-2022 "Determination of Hardness of Paint Film by Pencil Method".

[0061] 2. Transmittance Test: A 10μm thick adhesive film was coated onto a thin polyethylene terephthalate (PET) substrate as described above. Another PET substrate layer was then deposited on top to form a laminate. The laminate was then photocured. Using an Agilent Cary 300 UV-Vis spectrophotometer and with air as a reference, the transmittance of the cured laminate at a wavelength of 400nm was measured.

[0062] 3. Ultraviolet Aging Test: The prepared laminate was placed in an ultraviolet aging test chamber equipped with a UVA-340 light source, and subjected to an ultraviolet aging test at 0.76 W / (m²). 2 After 1000 hours of UV aging under irradiance of ·nm), its transmittance and color difference Δb with brand new white paper were measured using a spectrophotometer.

[0063] 4. Water vapor transmission rate test: The test was conducted in accordance with GB / T 1037 "Determination of water vapor transmission performance of plastic films and sheets". The water vapor transmission performance of a 1mm thick UV-cured sealant film was tested using a Shandong Pucheng WVTR-RC6 water vapor transmission rate tester. The test conditions were: test temperature 50℃, test relative humidity 90%RH, and test time 24h.

[0064] 5. Adhesion performance test: The encapsulated bonding sheet was placed in a high temperature and high humidity chamber at 85℃ and 85%RH for 1000 hours of aging, and then immersed in boiling red ink for 3 hours. The penetration of red ink into the encapsulation layer was observed under a microscope.

[0065] Table 1. Performance test results of the UV-curable quantum dot sealants prepared in Examples 1-10 and Comparative Examples 1-4.

[0066] As can be seen from the data in Table 1, compared with Comparative Examples 1 to 4, the UV-curable quantum dot sealants prepared in Examples 1 to 10 of the present invention have more suitable hardness and softness, higher light transmittance, and better weather resistance. After UV aging, the yellowing of the film is less and the light transmittance decay is lower. In addition, the UV-curable quantum dot sealants prepared in Examples 1 to 10 of the present invention can still maintain effective adhesion to polyethylene terephthalate substrates after humid heat aging. In some examples, zero ink penetration is achieved. At the same time, the water vapor transmission test results show that the UV-curable quantum dot sealants prepared in Examples 1 to 10 of the present invention can effectively block water and oxygen penetration. The above-mentioned effects are due to the following: On the one hand, by chemically copolymerizing terminal dihydroxyl silicone oil with isocyanate, flexible and hydrophobic organosilicon segments are embedded into the polyurethane backbone, which not only improves the flexibility and wetting and dispersibility of quantum dots in the UV-curable quantum dot sealant film, but also endows it with excellent resistance to UV degradation. On the other hand, by using self-made diol to graft long unsaturated side chains onto the polyurethane molecular chain, the photoactive groups are densely distributed along the side chains at multiple points. After curing, a more dense three-dimensional cross-linked network is formed than that of the linear difunctional polyurethane acrylates in Comparative Examples 1 to 4, thereby significantly improving the water and oxygen barrier effect of the UV-curable quantum dot sealant. At the same time, the steric hindrance effect of the side chains effectively isolates quantum dots and prevents agglomeration quenching. The synergistic effect of high cross-linking density and flexible backbone fully buffers curing shrinkage and hygrothermal stress, ensuring that the UV-curable quantum dot sealant film does not become brittle or debond during long-term aging. In summary, this invention fundamentally solves the technical challenge of existing commercially available linear polyurethane resins in achieving a balance between quantum dot dispersibility, weather resistance, adhesion reliability, and water and oxygen barrier properties by performing dual modifications on the polyurethane molecular structure through "organosilicon block chemical modification" and "long-chain high crosslinking," thus achieving a significant synergistic effect.

[0067] To further investigate the stability of the UV-curable quantum dot sealants prepared in Examples 1-10 and Comparative Examples 1-4 under long-term use or extreme conditions, the environmental reliability of the UV-curable quantum dot sealants prepared in Examples 1-10 and Comparative Examples 1-4 was tested. The specific test results are shown in Table 2, and the specific test methods are as follows: 1. High temperature and high humidity aging test: The prepared bonding sheet was placed in a constant temperature and humidity test chamber at 85℃ and 85% relative humidity for 1000h, and the changes at the sealing area were observed using a magnifying glass.

[0068] 2. Thermal shock cycle test: Place the sample in the basket of the thermal shock tester, set the temperature of the high temperature chamber to 85℃ and the temperature of the low temperature chamber to -40℃, and perform cold and heat treatment for half an hour each, for a total of 1000 cycles.

[0069] 3. High-temperature storage experiment: The prepared bonding sheet was placed in a constant temperature chamber at 85℃ and kept at that temperature for 1000h.

[0070] 4. Low-temperature storage experiment: The prepared bonding sheet was placed in a low-temperature chamber at -40℃ and kept at that temperature for 1000h.

[0071] 5. UV aging test: The prepared lamination sheet was placed in a UV aging chamber and continuously irradiated with ultraviolet light for 1000 hours.

[0072] Table 2. Environmental reliability tests of the UV-curable quantum dot sealants prepared in Examples 1-10 and Comparative Examples 1-4.

[0073] As shown in Table 2, the UV-curable quantum dot sealants prepared in Examples 1-10 of this invention outperform those in Comparative Examples 1-4. The main reason for this is that: this invention uses the chemical copolymerization of terminal dihydroxyl silicone oil and isocyanate to embed flexible dimethylsiloxane organosilicon segments into the polyurethane backbone, forming an organosilicon-modified polyurethane resin. Because the dimethylsiloxane segments possess heat resistance, cold resistance, flexibility, chemical stability, and a low glass transition temperature, the UV-curable quantum dot sealant does not degrade, yellow, or powder and delaminate during high-temperature and low-temperature storage and thermal shock tests. The high flexibility of the segments allows the UV-curable quantum dot sealant to release thermal stress promptly under thermal shock, thus preventing stress delamination. The stable chemical properties of the dimethylsiloxane segments also prevent chain breakage and oxidation under ultraviolet light irradiation, thereby improving the UV-curable quantum dot sealant's resistance to ultraviolet degradation. This allows the UV-curable quantum dot sealant prepared by this invention to meet actual production needs.

[0074] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described in this invention to avoid redundancy. Although preferred embodiments of this invention have been described, those skilled in the art, once they understand the inventive concept of this invention, can make other changes and modifications to these embodiments, and all such changes and modifications fall within the scope of this invention.

[0075] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. If such modifications and variations fall within the scope of equivalents of this invention, then this invention is also intended to include such modifications and variations.

Claims

1. A UV-curable quantum dot sealant, characterized in that, By weight, it comprises the following components: 60-80 parts of silicone-modified polyurethane resin, 20-40 parts of reactive diluent, and 0.3-0.6 parts of photoinitiator; The preparation method of the organosilicon-modified polyurethane resin includes the following steps: Weigh the following raw materials according to the following weight proportions: 20-50 parts isocyanate, 40-80 parts polyether polyol, 30-30 parts diol, 10-30 parts terminal dihydroxyl silicone oil, 0.1-1 part catalyst, 0.1-1 part polymerization inhibitor, 0.1-0.5 parts antioxidant, and 3-6 parts end-capping agent; The polyether polyol was subjected to vacuum dehydration and cooled for later use. Isocyanate, vacuum-dehydrated polyether polyol, terminal dihydroxyl silicone oil, polymerization inhibitor, antioxidant and catalyst are mixed evenly and then heated to react to obtain prepolymer; Diol is slowly added dropwise to the prepolymer, and the reaction continues. When the mass percentage of isocyanate groups in the system is 1% to 2%, an end-capping agent is added to the system. The reaction continues until the isocyanate groups are completely consumed. The unreacted end-capping agent is removed under reduced pressure to obtain the silicone-modified polyurethane resin.

2. The UV-curable quantum dot sealant according to claim 1, characterized in that, The conditions for vacuum dehydration of polyether polyols are: first, vacuum dehydration at 120℃ for 3-4 hours, and then cooling to 60℃-70℃.

3. The UV-curable quantum dot sealant according to claim 1, characterized in that, Isocyanate, vacuum-dehydrated polyether polyol, terminal hydroxyl silicone oil, polymerization inhibitor, antioxidant and catalyst are first mixed evenly at 60℃~75℃, and then heated to 85℃ and kept at the temperature for 2 hours to obtain prepolymer.

4. The UV-curable quantum dot sealant according to claim 1, characterized in that, The reactive diluent is selected from one or more of isobornyl acrylate, dicyclopentadiene acrylate, tricyclodecanediethanol diacrylate, tetrahydrofuran acrylate, cyclotrimethylolpropane acetal acrylate, dicyclopentadiene methacrylate, ethylene glycol dicyclopentenyl ether acrylate, dicyclopentadiene oxyethyl acrylate, and tricyclodecanediethanol diacrylate; the photoinitiator is selected from one or more of 2-hydroxy-2-methylphenylacetone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 1-hydroxy-cyclohexyl-phenyl ketone.

5. The UV-curable quantum dot sealant according to claim 1, characterized in that, The isocyanate is selected from one or more of isoflurane diisocyanate, hexamethylene diisocyanate, 4,4-diisocyanate dicyclohexylmethane, tetramethyl isophthalimethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, isophthalic dimethyl diisocyanate, and naphthalene 1,5-diisocyanate; the polyether polyol has an average molecular weight of 400-2000 and is selected from one or more of polypropylene glycol, polyethylene glycol, polytetrahydrofuran glycol, and polypropylene oxide.

6. The UV-curable quantum dot sealant according to claim 1, characterized in that, The terminal hydroxyl silicone oil is selected from one or two of hydroxyalkyl-terminated polydimethylsiloxane and α,ω-dihydroxypolydimethylsiloxane; the catalyst is selected from at least one of organometallic catalysts including stannous isooctanoate, stannous octanoate, dibutyltin dilaurate, bismuth isooctanoate, bismuth laurate, bismuth neodecanoate, and tetraisopropyl titanate; the end-capping agent is selected from one or more of ethanol, n-propanol, 2-(tert-butylamino)ethyl methacrylate, hydroxyethyl acrylate, and hydroxyethyl methacrylate.

7. The UV-curable quantum dot sealant according to claim 1, characterized in that, The preparation method of the diol includes the following steps: Weigh the following raw materials in the indicated weight proportions: 25-50 parts of bio-based dicarboxylic acid, 50-100 parts of glycidyl oleate, 0.1-1 part of catalyst, 0.1-0.5 parts of polymerization inhibitor, and 0.1-0.5 parts of antioxidant, wherein the molar ratio of bio-based dicarboxylic acid to glycidyl oleate is 1:2; After vacuum dehydration of the bio-based dicarboxylic acid, it is mixed with glycidyl oleate, polymerization inhibitor, antioxidant and catalyst 1. Under inert gas protection, the mixture is reacted at 105℃ for 1-2 hours until the system is homogeneous. Then the temperature is raised to 110℃ and held for 3-4 hours. Finally, the temperature is lowered to 85℃-95℃ and the reaction is carried out under reduced pressure for 1 hour to obtain the diol.

8. The UV-curable quantum dot sealant according to claim 7, characterized in that, The bio-based dicarboxylic acid is selected from one or more of succinic acid, glutaric acid, lauryl acid, sebacic acid, and itaconic acid; the glycidyl oleate is 2,3-epoxypropyl octadecenoic acid; the catalyst 1 is selected from at least one of triphenylphosphine, tetrabutylammonium bromide, triethylbenzylammonium bromide, and phenyltrimethylammonium bromide.

9. The UV-curable quantum dot sealant according to claim 7, characterized in that, The polymerization inhibitor is selected from one or more of p-methoxyphenol, hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, and bisphenol A; the antioxidant is selected from one or more of antioxidant 2246, antioxidant 1076, antioxidant 1010, and antioxidant 168.

10. A method for preparing a UV-curable quantum dot sealant as described in any one of claims 1 to 9, characterized in that, The process includes the following steps: mixing silicone-modified polyurethane resin, reactive diluent, and photoinitiator evenly according to the above-mentioned weight proportions to obtain a UV-curable quantum dot sealant.

Citation Information

Patent Citations

  • Sealant special for quantum dot packaging and preparation method thereof

    CN110527436A